Unusual diffuse cervicothoracofacial cellulitis of dental origin - Ousmane Belem; Rachid Aloua; Jacques Boa; Salissou Iro; Abel Mahoussi Bah; Sayouba Savadogo; Ouassime Kerdoud; Faiçal Slimani; Tarcissus Konsem (Elsevier, 2021)
Introduction: Diffuse cellulitis is a serious and potentially fatal condition. The etiology is most often dental. The aim of this work is to highlight the morbidity of diffuse cellulitis and the associated therapeutic difficulties, by reporting a serious, unusual case of diffuse cervico-thoracofacial cellulitis of dental origin. Observation: A 37-year-old patient with no particular pathological history presented with 48 odontalgia evolving for two weeks. The patient self-medicated of unspecified nature. He developed a secondary infection of the cellulosic fatty tissues of the lodges which spread to the cervical region and then to the thorax and the right forearm. Large areas of skin necrosis appeared, associated with an alteration of the general condition and motivated the consultation. The diagnosis of diffuse cervico-thoracofacial cellulitis was retained. Biological tests showed hyperleukocytosis with a predominance of neutrophils. Treatment consisted of resuscitation, synergistic tri-antibiotic therapy, and iterative removal of dead tissue under general anesthesia. Avulsion of the causal tooth was performed. The evolution was favorable after one month of hospitalization. Conclusion: Diffuse cellulitis is serious and is prognostic for the patient. The management is urgent and multidisciplinary.